Pediatric Boot Camp Series: Longitudinal Care for a Child With Asthma—From the Emergency Department to Outpatient Clinic - James Metz (Association of American Medical Colleges, 2020)
Introduction Childhood asthma is a major source of worldwide morbidity and mortality. Successful management requires a broad spectrum of skills. Given the prevalence, medical students should be proficient in evaluating and managing asthma, including the acute treatment of an exacerbation through the maintenance phase. Methods We used a high-fidelity simulation case of a 2-year-old boy presenting to the emergency room in respiratory distress to let medical students practice the assessment and management of a patient in status asthmaticus. Small-group, case-based discussions combined with provider/parent role-playing facilitated building a framework for addressing the medical management and social aspects of asthma control. Large-group discussions and review of national asthma guidelines helped solidify the material. Results Forty-one fourth-year medical students participated in this curriculum over a 5-year period. All participants strongly agreed with the statement “I took away ideas that I plan to apply to internship.” Using a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree), the mean agreement with the statement “This simulation session and debrief was useful” was 5 and with “The small-group role-play and discussions were useful” was 4.5. Students reported that they had a better framework for the treatment and management of asthma. Discussion This curriculum is unique in that it uses one unifying case through different phases of care to allow participants to demonstrate comprehensive management of childhood asthma in various practice settings. The curriculum can be used independently or in conjunction with other learning activities as part of a pediatric boot camp.